(untitled) (Academicia Globe: Inderscience Research, 2022)
One of the key terms of modern cognitive linguistics and linguoculturology is the concept. It has been attracting the attention of those interested in the problems of human thinking and construction. Analyzing the different views on the nature of the concept, the scientists came to a clear conclusion: the concept is not a type of abstract names, but the main angle of study of knowledge and skills accumulated by the people over the centuries. Recently, the number of scientific studies devoted to the study of the concept is growing. In modern linguistics, the study of the nature of a concept plays a primary role. The point is that there is a concept, but at the present time it is one of the problems awaiting its study. More about this source textSource text required for additional translation information